Prevalence of caries according to ceod index in 6 years old school children of Cuenca-Ecuador - Veléz, Eleonor (2019)
Objective: Determine the ceod on school children of six years of age in the parish of El Sagrario-Cuenca in the year 2016. Materials and Methods: A descriptive, transversal, retrospectivestudy was carried out, the sample consisted of 163 epidemiological records corresponding to 6-year-old patients, of which 55% were female and 45% were male, pertaining to public schools at El Sagrariodistrict. Results: The results obtained show that the average ceod index in the school children of six years of age at El Sagrario district is of 4.9.Which did not have significant differences between males and females presenting values between 4.5 and 4.9 respectively. Conclusions: Based on the levels of severity of World Health Organization(OMS), the study group shows a high risk of cavities